Tác động của sáng tạo cá nhân với dự định và hành vi khởi nghiệp - Nguyễn Thu, Thủy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The current research on entrepreneurship lacks studies on entrepreneurial behavior and the relationship between entrepreneurial intention and entrepreneurial behavior. This study examines the impact of individual creativity on entrepreneurial behavior of university students in Vietnam based on the model of planned behavior (TPB). The research sample includes 701 university students in both technical and economic-business management in Hanoi. The survey results show that creativity has an influence on students' attitudes, perceived control behavior, entrepreneurial intention, and entrepreneurial behavior, and moderates the relationship between entrepreneurial intention and behavior.
Keywords: Entrepreneurship intention; Entrepreneurship behavior; Theory of Planned Behavior (TPB); Creativity